Cumulative live birth rate of advanced-age women more than 40 with or without poor ovarian response - Huiqun Yin; Hong Jiang; Ruibing He; Cunli Wang; Jie Zhu; Zhenyi Cao (Elsevier, 2019)
Objective: The aim of this study was to investigate cumulative live birth rate (CLBR) per oocyte retrieval cycle and per patient in women over 40 years old undergoing IVF/ICSI treatments, stratified for age, ovarian response and oocyte retrieval cycle number. Materials and methods: 244 patients with poor ovarian response (POR) and 372 patients with normal ovarian response (NOR) were retrospectively investigated. Results: Of the patients aged 40 to 43 years, CLBR per oocyte retrieval cycle and per patient (4.3%; 8.8%) in POR group were both lower than those in NOR group (15.8%; 24.8%) (P < 0.01). No significant differences in live birth rate (LBR) per oocyte retrieval cycle or CLBR per patient were observed in the group of POR patients irrespective of oocyte retrieval cycles they underwent. Similarly, CLBR per patient in NOR group did not increase significantly with the oocyte retrieval cycle number. However, LBR per oocyte retrieval cycle in the first cycle (Cycle 1, 20.3%) was significantly higher than that in the second cycle (Cycle 2, 9.2%) and the third cycle (Cycle 3, 4.4%) (P < 0.01). And 94.8% (73/77) of live births were achieved during the first two cycles. Of the patients aged 44 to 45 years and over 45 years old, there were no significant differences in CLBR per oocyte retrieval cycle or per patient between POR and NOR groups. Conclusion: Relatively higher cumulative live birth rate was only found in the patients aged 40 to 43 years without poor ovarian response. These findings may provide some information that further sub-classification of advance-age women according to ovarian response may help both clinicians and patients to balance decision-making about their infertility treatment. Keywords: Advanced maternal age, Cumulative live birth rate, Poor ovarian response